2016
DOI: 10.4048/jbc.2016.19.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Programmed Death Receptor Ligand 1 with High Tumor-Infiltrating Lymphocytes Is Associated with Better Prognosis in Breast Cancer

Abstract: PurposeThe interaction of programmed death receptor 1 (PD-1) and its ligand, programmed death receptor ligand 1 (PD-L1), negatively regulates immune responses. This study aimed to clarify PD-L1 expression levels in breast cancer through immunohistochemistry (IHC) and to evaluate associations between these findings and clinicopathologic variables, including prognosis.MethodsPD-L1 expression was analyzed using IHC on tissue microarrays of 465 invasive breast carcinomas.ResultsHigh PD-L1 expression was demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 30 publications
11
52
2
1
Order By: Relevance
“…No statistically significant associations were found between PDL1TC and other clinicopathologic parameters. These findings are consistent with most studies found in the literature (43)(44)(45)(46). The association between PDL1TC and HER2 status remains controversial, though (41,47).…”
Section: Figure 1 (A) Pd-l1 Expression In Tumor Cells (×20) (B) Pd-supporting
confidence: 92%
“…No statistically significant associations were found between PDL1TC and other clinicopathologic parameters. These findings are consistent with most studies found in the literature (43)(44)(45)(46). The association between PDL1TC and HER2 status remains controversial, though (41,47).…”
Section: Figure 1 (A) Pd-l1 Expression In Tumor Cells (×20) (B) Pd-supporting
confidence: 92%
“…Recently, the combination of PD‐L1 and tumor‐infiltrating lymphocytes (TILs) has been investigated in TNBC, and the reported findings confirm the importance of examining both PD‐L1 and TILs for clinical outcome prediction . In the current study, we evaluated PD‐L1 and a set of other relevant immune markers in relation to their association with clinical outcome in a series of HER2‐positive cases.…”
Section: Introductionmentioning
confidence: 69%
“…There have been conflicting results in the literature as to whether PD‐L1 expression is a favorable or adverse prognostic factor for breast cancer patients managed with standard therapy. Most of the published studies have dealt with patients with diverse subtypes of breast cancer, with the exception of several studies which focused on TNBC exclusively . The discordance of reported results may relate to differences in methods of assessment, numeric thresholds, antibody clones or composition of cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PD‐L1 expression has been positively and independently associated with DFS/RFS and/or OS in several unselected primary BC cohorts . In addition, when considering specific BC subtypes, it has been suggested that PD‐L1 protein expression may retain a positive prognostic role in TNBC and in HER2+ BC, in both trastuzumab‐treated and untreated patients .…”
Section: Methodsmentioning
confidence: 99%